Review of the genus Ammobatoides Radoszkowski, 1867 (Hymenoptera: Apidae, Nomadinae) from Russia and neighbouring countries - Proshchalykin, Maxim Yu.; Lelej, Arkady S. (Zootaxa, 2014)
Three species of Ammobatoides are reviewed. One new species, Ammobatoides radoszkowskii sp. nov. (Russia and North China) is described and illustrated. A male lectotype is designated for Paidia melectoides Radoszkowski, 1872. One new subjective synonym is established: Ammobatoides scriptus (Gerstaecker, 1869) =Paidia melectoides Radoszkowski, 1872, syn. nov. A key to species for both sexes is given.